INCIDENCE, SECULAR TRENDS AND OUTCOMES OF PROSTHETIC JOINT INFECTION (PJI): A POPULATION BASED STUDY, OLMSTED COUNTY, MINNESOTA, 1969 – 2007 - Tsaras, Geoffrey (2012)
CONTEXT: The epidemiology of prosthetic joint infection (PJI) in a population based cohort has not been studied in the United States. OBJECTIVES: To provide an accurate assessment of the true incidence, secular trends, clinical manifestations, microbiology and treatment outcomes of PJI in a population based cohort. DESIGN: Historical cohort study SETTING: Olmsted County, Minnesota, United States of America. PARTICIPANTS: Residents who underwent total knee arthroplasty (TKA) or total hip arthroplasty (THA) between 1/ 1/ 1969 and 12/ 31/ 2007. METHODS: Incidence rates and trends in PJI were assessed using the Kaplan Meier method and log-rank test, as were treatment outcomes among PJI cases. RESULTS: 7375 THA or TKA were implanted in residents of Olmsted County during the study period. Seventy five discrete joints in 70 individuals developed PJI, during a mean(+/− SD) follow up of 6.8 (+/− 6.1) years. The cumulative incidence of PJI was 0.5%, 0.8% and 1.4% after 1, 5 and 10 years following arthroplasty, respectively. Overall, the rate of survival free of clinical failure after treatment of PJI was 76.8 % ( 95% CI: 64.3 – 85.2) and 65.2 % ( 95% CI: 33.1 – 76.2) at 3 years and 5 years, respectively. The incidence and treatment outcomes did not significantly differ by decade of implantation, patient age at implantation, gender or joint location. CONCLUSIONS: The incidence of PJI is relatively low in a population based cohort, and is a function of age of the prosthesis. Incidence trends and outcomes have not significantly changed over the past forty years.